2022
DOI: 10.1017/s1478951522001110
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and understanding death anxiety in caregivers of patients with primary brain tumor

Abstract: Objective Caregivers of patients with primary brain tumor (PBT) describe feeling preoccupied with the inevitability of their loved one's death. However, there are currently no validated instruments to assess death anxiety in caregivers. This study sought to examine (1) the psychometric properties of the Death and Dying Distress Scale (DADDS), adapted for caregivers (DADDS-CG), and (2) the prevalence and correlates of death anxiety in caregivers of patients with PBT. Methods Caregivers (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Such anxiety may include fear of not knowing what may happen at the end of life, fear of being alone after the death of the patient, fear that the patient may suffer as the disease progresses, or fear of not having enough shared time left. 61 Our results further indicate that high levels of death anxiety significantly affect family caregivers' quality of life; by interfering with caregivers' psychological adjustment, it can strain the relationship between the family caregiver and the patient, 62 and increase the challenge of providing the necessary support and care that is needed. Psychosocial support for caregivers may address emotional support and advice on caring and thus lead to better quality of life and increased ability of coping with the caring role.…”
Section: Study Locationmentioning
confidence: 58%
See 1 more Smart Citation
“…Such anxiety may include fear of not knowing what may happen at the end of life, fear of being alone after the death of the patient, fear that the patient may suffer as the disease progresses, or fear of not having enough shared time left. 61 Our results further indicate that high levels of death anxiety significantly affect family caregivers' quality of life; by interfering with caregivers' psychological adjustment, it can strain the relationship between the family caregiver and the patient, 62 and increase the challenge of providing the necessary support and care that is needed. Psychosocial support for caregivers may address emotional support and advice on caring and thus lead to better quality of life and increased ability of coping with the caring role.…”
Section: Study Locationmentioning
confidence: 58%
“…The latter study found anxiety regarding the patient's death as a central existential theme associated with the progression of the patient's disease. Such anxiety may include fear of not knowing what may happen at the end of life, fear of being alone after the death of the patient, fear that the patient may suffer as the disease progresses, or fear of not having enough shared time left 61 . Our results further indicate that high levels of death anxiety significantly affect family caregivers' quality of life; by interfering with caregivers' psychological adjustment, it can strain the relationship between the family caregiver and the patient, 62 and increase the challenge of providing the necessary support and care that is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Considering sociodemographic factors, only in two studies were higher levels of death anxiety found in women [28,61], indicating that it is not an exclusive risk variable (see Table 2). This could be due to the fact that this relationship only occurs in very specific areas or contexts and not universally across all settings [67,68].…”
Section: Discussionmentioning
confidence: 97%
“…Perceived social support is also identified as an explanatory factor for greater or lower levels of death anxiety in some studies [59]. It also varies depending on the illness, as exemplified in the study of Willis et al [61], where this anxiety was notably high in female caregivers of terminally ill patients. Lastly, the strong correlation found in one study [50], between this type of anxiety and post-traumatic growth cannot be ignored.…”
Section: Death Anxiety and Related Factorsmentioning
confidence: 96%